Mobility Trope: Travelling as a Signature of the Afropolitan Female Quest for Existential Subjectivity in Chika Unigwe’s On Black Sisters’ Street - Anasiudu, Okwudiri (Journal of Gender and Power, 2021)
The mobility trope is a key aesthetic feature in Afropolitan fiction and it crystalizes as the act of travelling which has become an important subject-matter in postnationalist African fictions by women such as Chimamanda Adichie, Noviolet Bulawayo or Chika Unigwe as a way of intervention on the debate of the Afropolitan female quest for existential subjectivity in 21st century African fiction. This is against the backdrop of negative essentialism and the exertions of patriarchy evident in the representation of African women’s in 20th century African fiction. Drawing from the foregoing, this paper interrogates Chika Unigwe’s On Black Sisters’ Street (Hence OBSS) to demonstrate how the writer deploys mobility trope which manifest as travelling as a signature of the Afropolitan female quest for existential subjectivity. I argue in this paper that, though existing studies on OBSS portray Efe, Sisi, Ama and Joyce as exported commodities in neoliberal sex market, their relocation however opens up a new vista to understanding their motivation and quest for new subjectivity, empowered fluid agency, individual autonomy and translation into Afropolitans. This is within Achille Mbembe’s phenomenological criticism of Afropolitanism and a methology that is based on qualitative content analysis of the text—OBSS. On the long run, the identity which travelling confers on the female characters is fluid, as they represent an African being in a globalized world and a strong sense of cultural mobility.